2006
DOI: 10.1016/j.cub.2006.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase Promotes Turnover of Kinetochore Microtubules to Reduce Chromosome Segregation Errors

Abstract: Merotelic kinetochore orientation is a misattachment in which a single kinetochore binds microtubules from both spindle poles rather than just one and can produce anaphase lagging chromosomes, a major source of aneuploidy. Merotelic kinetochore orientation occurs frequently in early mitosis, does not block chromosome alignment at the metaphase plate, and is not detected by the spindle checkpoint. However, microtubules to the incorrect pole are usually significantly reduced or eliminated before anaphase. We dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
408
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 365 publications
(440 citation statements)
references
References 36 publications
27
408
2
3
Order By: Relevance
“…Previous work estimated that ϳ70% of the MTs were in nonkt-spindle MTs and 30% were in K-fibers (Mitchison and Salmon, 1992;Cimini et al, 2006). However, in our study we observed that only 20% of the recovery comes from the nonkt-spindle MTs and 80% is from the K-fibers.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Previous work estimated that ϳ70% of the MTs were in nonkt-spindle MTs and 30% were in K-fibers (Mitchison and Salmon, 1992;Cimini et al, 2006). However, in our study we observed that only 20% of the recovery comes from the nonkt-spindle MTs and 80% is from the K-fibers.…”
Section: Discussioncontrasting
confidence: 77%
“…Our measured t 1/2 values for the slow phase of the recovery for prometaphase cells are similar to those reported previously for the K-fibers . Our values for the fast phase, however, are faster than those reported by others (Saxton et al, 1984;Zhai et al, 1995;Cimini et al, 2006). One possibility is that our fast phase actually represents the diffusion of unincorporated GFP-tubulin subunits into the bleach zone.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations